2018
DOI: 10.17245/jdapm.2018.18.4.267
|View full text |Cite
|
Sign up to set email alerts
|

Migrating foreign body in an adult bronchus: An aspirated denture

Abstract: As a safety measure, dentures are routinely removed before surgery. Aspiration of a denture could be catastrophic, with medicolegal implications. Foreign body aspiration is uncommon in adults; however, aspirations may remain asymptomatic and undiagnosed for long periods of time. We report an adult male who presented with a cough for more than 6 months. On radiography, a foreign body was found migrating within the tracheobronchial tree from one mainstem bronchus to the other, at different time points. The forei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Additionally, Molina and other scholars' research on tumor markers indicated that the sensitivity is not high in lung cancer diagnosis with only increased CEA, especially for non-small-cell lung cancer. It is concluded that CEA is not a unique marker for the lung cancer 9,16,17. In this case, after the operation of removing the foreign body, the patient pul-monary infection was under control and CEA level was normal after 2 weeks later.…”
mentioning
confidence: 79%
“…Additionally, Molina and other scholars' research on tumor markers indicated that the sensitivity is not high in lung cancer diagnosis with only increased CEA, especially for non-small-cell lung cancer. It is concluded that CEA is not a unique marker for the lung cancer 9,16,17. In this case, after the operation of removing the foreign body, the patient pul-monary infection was under control and CEA level was normal after 2 weeks later.…”
mentioning
confidence: 79%
“…7,8 Rarely, as in the present case, aspiration may produce minimal or no symptoms. 3 Cough is a very common symptom in patients with an aspirated FB. 3 Inorganic materials such as those in a denture cause little tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…3 Cough is a very common symptom in patients with an aspirated FB. 3 Inorganic materials such as those in a denture cause little tissue inflammation. On the contrary organic aspirated materials present with symptoms due to the inflammatory reaction around them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations